2020
DOI: 10.1021/acs.jmedchem.0c00137
|View full text |Cite
|
Sign up to set email alerts
|

CN128: A New Orally Active Hydroxypyridinone Iron Chelator

Abstract: Deferoxamine, deferiprone, and deferasirox are used for the treatment of systemic iron overload, although they possess limitations due to lack of oral activity, lower efficacy, and side effects. These limitations led to a search for an orally active iron chelator with an improved therapeutic index. The lower efficacy of deferiprone is due to rapid glucuronidation, leading to the formation of a nonchelating metabolite. Here, we demonstrate that the influence of metabolism can be reduced by introducing a sacrifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…To further understand the drug-likeness, the molecular properties of these new hybrids were predicted and performed by molinspiration ( http://www.molinspiration.com ). It was found that miLog p -values of HPOs were closer to the experimentally measured values than those calculated by other programs 33 . All the compounds were in accordance with Lipinski’s rules and Veber’s rules.…”
Section: Resultssupporting
confidence: 48%
“…To further understand the drug-likeness, the molecular properties of these new hybrids were predicted and performed by molinspiration ( http://www.molinspiration.com ). It was found that miLog p -values of HPOs were closer to the experimentally measured values than those calculated by other programs 33 . All the compounds were in accordance with Lipinski’s rules and Veber’s rules.…”
Section: Resultssupporting
confidence: 48%
“…These would include iron mobilization, free-radical scavenging and the anti-proliferative effects of Fao cells when compared to DFP [ 27 , 28 ]. Currently, a novel synthetic bidentate amino alcohol-conjugated HPO chelator has been reported as being more lipophilic and efficient in terms of iron-binding affinity than the parent DFP (log P o / w values for free ligands = 0.56 versus −0.77; log P o / w values for [Fe-L 3 ] = 0.58 versus −2.6; iron-mobilizing efficacy in rats = 24.8 versus 11.8%, respectively); nevertheless, this chelator has never been assessed for anti-malarial activity, either in vitro or in vivo [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A log P-guided investigation of 20 hydroxpyridinones resulted in the identification of CN128. A study by Chen et al [ 155 ] showed that the Fe(III) affinity and metal selectivity of CN128 are similar to those of DFP, the log p value is more lipophilic, and its iron scavenging ability is superior. It was concluded that CN128 was safe in a range of toxicity assessments and is currently used in clinical trials for the treatment of β -thalassemia after regular blood transfusion.…”
Section: Combined Therapy With More Than One Chelatormentioning
confidence: 99%